Calcium triggered arrhythmias and the Goldilocks’ principle - Valverde, Carlos Alfredo (2024)
Beyond the importance of calcium cycling on cardiac contractile function, calcium can also affect membrane currents and lead to arrhythmias. In this revision we will discuss how the balance between release and reuptake of calcium from and to the sarcoplasmic reticulum affects the probability of arrhythmias. A mathematical human cardiomyocyte model that can simulate increasing RyR2 open probabilities (Po) along with high or low SERCA2A mediated reuptake velocities showed that arrhythmias occur in an intermediate physiological zone for both RyR2 Po and reuptake velocity. These results allow to make a parallelism with the “goldilocks and the tree bears” story in which she is looking to drink a cup of porridge with an intermediate optimal temperature. Along the text we explain how the Goldilocks principle is fulfilled in different well-known experimental situations.